HISTORY OF INNOVATION IN THE PRESENTATION OF SITAR (WITH REFERENCE TO ETAWAH AND MAIHAR GHARANA): सितार के प्रस्तुतिकरण में नवाचार का इतिहास (इटावा तथा मैहर घराने के विष्¨ष संदर्भ में) - Thakur, Harshvardhan; Dubey, Rupashree (International Journal of Research -GRANTHAALAYAH, 2015)
Various Vedic period music texts such as Rigveda, Samveda, Shakhayana Brahmin, Shatapatha Brahmin etc. Apart from Ramayana, Mahabharata, the Lankar Purana tradition and the Natasha language of Bharata and Abhinav Bharati, Sangeet Ratnakar etc. Get a description of. Later, in the texts of music Damadar, Aine Akbari, Raga Vibandh, Sangeet Parijat, Radhagavind Sangeet Saar etc., four types of instruments are also found in the medieval and 19th century texts. It is noteworthy that the mention of veena is found in the above texts, from which it can be said that since ancient times the veena instrument has played an important place in Indian music. The proof of the consistency of singing till the middle ages in India is evident based on the material presented in the texts like Sangeet Ratnakar, Chaturdandi Prakasika, Sangeet Parijat etc. Even after following the vocals, they have maintained their separate independent existence in instrumental playing. This is the reason that the practice of free speech started taking shape in the instruments of the 18th century Vichitra Veena, Rudra Veena, Sur-Bahar, Sursingar, Sitar etc. Later, the sitar defeated all the instruments and gained a prominent position and earned an immense reputation as a soloist playing solo. In these years of travel, not only the ancient form of the sitar instrument has changed, but its speech has also seen substantial changes. विभिन्न वैदिक कालीन संगीत ग्रंथ¨ं यथा ऋग्वेद, सामवेद, षाखायण ब्राह्मण, षतपथ ब्राह्मण आदि के अलावा रामायण, महाभारत से ल्¨कर पुराण परंपरा तथा भरत के नाट््य षाó एवं अभिनव भारती, संगीत रत्नाकर आदि समस्त ग्रंथ¨ं में तंत्र्ाी वाद्य¨ं का वर्णन मिलता है। आगे चलकर संगीत दाम¨दर, आइने अकबरी, राग विब¨ध, संगीत पारिजात, राधाग¨विंद संगीत सार आदि, मध्यकालीन एवं 19वीं षती के ग्रंथ¨ं में भी चार प्रकार के वाद्य¨ं का वर्णन मिलता है। उल्ल्¨खनीय है कि उपर¨क्त ग्रंथ¨ं में वीणा का उल्ल्¨ख पाया जाता है जिससे यह कहा जा सकता है कि प्राचीनकाल से ही वीणा वाद्य का भारतीय संगीत में महत्वपूर्ण स्थान रहा है। भारत वर्ष में मध्य युग तक गायन की संगति का प्रमाण संगीत रत्नाकर, चतुर्दण्डी प्रकाषिका, संगीत पारिजात आदि ग्रंथ¨ं में प्रस्तुत सामग्री के आधार पर स्पष्ट ह¨ जाता है। कंठ का अनुगमन करने के बाद भी वाद्य वादन में अपना अलग स्वतंत्र्ा अस्तित्व भी बनाये रखा है। यही कारण है कि 18वीं षताब्दी की विचित्र्ा वीणा, रुद्र वीणा, सुर-बहार, सुरसिंगार, सितार आदि वाद्य¨ं में स्वतंत्र्ा वादन की प्रथा अपना आकार ल्¨ने लगी। आगे चलकर सभी वाद्य¨ं क¨ पछाड़ते हुए सितार ने एक प्रमुख स्थान प्राप्त किया अ©र एकल वादन में बजाए जाने वाल्¨ वाद्य के रूप में अपार प्रतिष्ठा अर्जित की। इन द¨ स© वषर्¨ं की यात्र्ाा में सितार वाद्य का ना केवल प्राचीन स्वरूप ही बदला वरन उसकी वादन ष्©ली में भी पर्याप्त रूप से परिवर्तन दृष्टिग¨चर ह¨ते हैं।